Kinetics of L-ascorbic acid degradation and non-enzymatic browning development in hot-compressed water - Feng, Liang; Yang, Yan; Xie, Ya-ting; Liu, Shuang-shuang; Peng, Xuan; Hu, Sheng; Yu, Ai-nong (Frontiers in Nutrition, 2023)
The effect of reaction parameters, which included the reaction temperature, time, concentration of L-ascorbic acid (ASA) and the solution pH, on the ASA degradation were investigated in hot compressed water (HCW). The degradation kinetics of ASA and generation kinetics of browning products (BPs) were studied. The results showed that the ASA degradation conformed to the pseudo-first-order kinetics, and the formation of BPs was closely related to the concentration of H3O+ in HCW. The kinetic model for formation of BPs was proposed according to the physical-chemistry and organic-chemistry theory. The acidic condition and lower concentration of ASA were more favorable for the ASA degradation. In HCW, the apparent activation energy (Ea) of ASA was 15.77, 31.70 and 47.53 kJ/mol at ranged of reaction pH. The possible degradation mechanisms of ASA and the generation of BPs in HCW were proposed according to the experimental results.